2006
DOI: 10.1186/1471-2393-6-15
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pre-pregnancy body mass index and gestational weight gain on pregnancy outcomes in urban care settings in Urmia-Iran

Abstract: BackgroundNutritional status of women has been considered an important prognostic indicator of pregnancy outcomes. Few studies have evaluated patterns of weight gain and pre-pregnancy body mass index in developing regions where malnutrition and poor weight gain as well as maternal obesity have significant influences on the pregnancy outcome. This study aims to show effect of pregnancy body mass index and the corresponding gestational weight gain on the outcome of pregnancy.MethodsOn a prospective cross section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
2
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 13 publications
1
36
2
3
Order By: Relevance
“…Pre-pregnancy BMI and gestational weight gain have been studied and found to have an important impact on the birth weight and future health of babies. 20,21 In the current study, underweight mothers or those who gained less weight than recommended had a two times greater risk of giving birth to LBW babies compared to women with a normal BMI. This finding is consistent with the results of other studies.…”
Section: Discussionmentioning
confidence: 93%
“…Pre-pregnancy BMI and gestational weight gain have been studied and found to have an important impact on the birth weight and future health of babies. 20,21 In the current study, underweight mothers or those who gained less weight than recommended had a two times greater risk of giving birth to LBW babies compared to women with a normal BMI. This finding is consistent with the results of other studies.…”
Section: Discussionmentioning
confidence: 93%
“…A literatura demonstra que os extremos do estado nutricional antropométrico podem trazer riscos adicionais à gestação [18][19][20][21] . Conhecer os detalhes do consumo dietético aprimora a qualidade do atendimento e das orientações fornecidas.…”
Section: Discussionunclassified
“…Em estudo com grávidas de uma região urbana do Irã 21 , mulheres com baixo peso pré-gestacional demonstram risco para ganho ponderal insuficiente na gravidez, e, nas gestantes obesas, o ganho ponderal excessivo é observado em 47,9%, proporção comparável ao presente estudo.…”
Section: Discussionunclassified
“…However, as pointed out in the available literature, the IOMrecommended method has been associated with favorable obstetric results related to birth-weight outcome as well as maternal health (14,20,33).…”
Section: Historic Evolution Of Methodsmentioning
confidence: 99%
“…Based on these recommendations, several authors have concluded that gestational weight values can help predict birth conditions as well as optimal maternal nutritional status in the postpartum period (14,33).…”
Section: Historic Evolution Of Methodsmentioning
confidence: 99%